KONDISI EKOSISTEM TERUMBU KARANG DI LOKASI TIATIKI DAN NON-TIAITIKI, KAMPUNG TABLANUSU DISTRIK DEPAPRE KABUPATEN JAYAPURA - Yunus Pajanjan Paulangan (Scripta Biologica, 2018)
Depapre Bay has large potential fisheries resources and very diverse that are still managed by the Tiaitiki system. Ironically, destructive fishing activities still occur. The coral ecosystems in Depapre Bay are still relatively under-studied mainly related to sustainable management. Condition of coral reef and reef fishes are the base aspect in management approach. The purpose of this research is to analyze coral reef and reef fishes condition of Tiatiki area and outside of Tiaitiki. The method used in this research is Point Intercept Transect (PIT) to identify coral condition, and Underwater Visual Cencus Method (UVC) for reef fishes observation. The results showed that lifeform conditions at 3-5 m of Tiaitiki area were "40,67% was moderate, dominated by Coral Branching, Flassy Micro Alga dan Coral Foliose; and  at 10-13 m of Tiaitiki area were 50,00% was “good”. Lifeform conditions at 3-5 m of non-Tiaitiki area were "48,67% was moderate, dominated by Coral Branching, Coral Massive dan Flassy Micro Alga; and  at 10-13 m of non-Tiaitiki area were 60,67% was “good”, dominated by Coral Branching, Acropora Branching, Acropora Tabulate, Acropora Encrusting dan Coral Foliose. In addition, at the all areas found rubbles is quite high at about 8-16,67%. Abundance of reef fishes in both areas is relatively the same, where in Tiaitiki area that are 372 individual at 3-5 m of depth and 114 individual at 10-13 m of depth, and Non-Tiaitiki area that are 262 individual at 3-5 m and 215 individual at 10-13 m.